Anorectal Gastrointestinal Stromal Tumor: About a Rare Case Report and Review of Literature - Hala, Aouroud; Rizkou, Jihane; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2022)
Gastrointestinal stromal tumor’s are the most common mesenchymal tumor of the gastrointestinal tract in adults; stromal tumors in the rectum are extremely rare. We report the case of a 64 years old woman admitted for admitted for etiological assessment of low-grade rectal bleeding and terminal appearance constipation, whose paraclinical investigations showed the presence of a GIST without secondary lesions with a high risk of recurrence and whose therapeutic decision was to start imatinib as a neoadjuvant treatment and then schedule her for a subsequent resection.